2019
DOI: 10.1016/j.healthpol.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting participation in health checkups: Evidence from Japanese survey data

Abstract: Multiple factors influence individuals to get health checkups. This study uses Japanese survey data to investigate key determinants of the health checkup decision. Relevant personal attributes and lifestyles are identified. The results indicate that the influence of these factors varies according to the type of health checkup. We also examine the impact of an individual's time preference on his/her health checkup behavior. The results suggest that hyperbolic discounters are more likely than non-hyperbolic disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 12 publications
2
22
1
Order By: Relevance
“…Although we showed no difference between gender in their intention to undergo CVD health checks, the factors influencing their intentions differed, with a strong influence of internal factors. Many studies that measured the impact of gender and factors on undergoing health checks focused mainly on sociodemographic factors [30,35,36] rather than a comprehensive evaluation of internal and external factors. Previous study had demonstrated a small but significant relationship between age, gender, social factors and health checks intention and behaviour, with variance explained by only less than 4% [37].…”
Section: Plos Onementioning
confidence: 99%
“…Although we showed no difference between gender in their intention to undergo CVD health checks, the factors influencing their intentions differed, with a strong influence of internal factors. Many studies that measured the impact of gender and factors on undergoing health checks focused mainly on sociodemographic factors [30,35,36] rather than a comprehensive evaluation of internal and external factors. Previous study had demonstrated a small but significant relationship between age, gender, social factors and health checks intention and behaviour, with variance explained by only less than 4% [37].…”
Section: Plos Onementioning
confidence: 99%
“…Because a Japanese study suggested that CKD screening using dipstick urinalysis and/or serum creatinine measurement was a cost-effective approach to prevent progression to ESKD 13 , the MHLW has encouraged adults aged ≥ 40 years to undergo CKD screening through the annual health checkup program, which includes dipstick urinalysis as a mandatory item and serum creatinine measurement as an optional item 14 . However, the proportion of the population undergoing health checkups is low at about 50% and 30% in adults aged 40–74 and ≥ 75 years, respectively 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Health checkups is a demand for health and lead to further demand for preventive or medical care when necessary [ 27 – 29 ]. Use of health check-up services depends on user’s characters and various other factors [ 27 ], that includes demographic, socioeconomic, personal health conditions, and the health care resources accessibility factors [ 18 , 30 , 31 ]. We also included the health behavior variable (life style) as an explanatory variable because it was demonstrated to be associated with health check-ups utilization [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Use of health check-up services depends on user’s characters and various other factors [ 27 ], that includes demographic, socioeconomic, personal health conditions, and the health care resources accessibility factors [ 18 , 30 , 31 ]. We also included the health behavior variable (life style) as an explanatory variable because it was demonstrated to be associated with health check-ups utilization [ 31 ]. This study selected the following explanatory variables for assessment: self-rated health, chronic disease status, and mobility difficulties (individual’s health factors), age, marital status, and educational level (proxies for demographic factors), the log of predicted income (income variable), and the number of physicians per 10,000 persons (as a proxy of health care resources accessibility factor).…”
Section: Methodsmentioning
confidence: 99%